Leader Emergence in Nascent Venture Teams: The Critical Roles of Individual Emotion Regulation and Team Emotions - Sirén, Charlotta; He, Vivianna Fang; Wesemann, Henrik; Jonassen, Zoe; Grichnik, Dietmar; von Krogh, Georg (Journal of Management Studies, 2020)
Abstract This study advances a theory of how different aspects of emotion regulation influence individual leader emergence in the intensely emotional context of nascent venture teams. Despite the growing amount of research on the role of leadership in the entrepreneurial process, the emergence of leaders in nascent venture teams has rarely been explored. Drawing on theories and research on leadership emergence and emotion regulation, we argue that the two aspects of emotion regulation (i.e., reappraisal and suppression) exert opposite effects on the degree to which nascent venture team members come to perceive an individual as a leader. We also theorize that team emotions arising from affective events moderate the relationship between reappraisal and leader emergence in such teams. Data from 103 nascent venture teams without prior leaders show a negative relationship between individuals’ trait disposition to suppress emotions and their emergence as leaders, and a positive relationship between their trait disposition to reappraise emotions and their emergence as leaders. Moreover, we find that negative team emotions magnify the positive association between reappraisal and leader emergence, while positive team emotions mitigate it. We discuss the implications of our findings for the literature on entrepreneurial leadership, entrepreneurial emotions, and leadership in general.